2019
DOI: 10.1002/mp.13923
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle enhanced proton therapy: A Monte Carlo simulation of the effects of proton energy, nanoparticle size, coating material, and coating thickness on dose and radiolysis yield

Abstract: Purpose Radiosensitizer enhanced radiotherapy provides the possibility of improved treatment outcomes by preferentially increasing the effectiveness of radiation within the tumor. Proton therapy offers improved sparing of tissue distal of the tumor along the beam path and reduced integral dose compared to conventional photon therapy. The combination of proton therapy with radiosensitizers offers the potential for an enhanced therapy with increased effect within the tumor and low integral dose. The simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…This is likely due to passivation of the solid liquid interfacial catalysis of radicals, and/or absorption of secondary electrons emitted from the nanoparticle within the coating layer. The latter mechanism was supported by data showing a decrease in yield with increasing coating atoms, and has been further supported by Monte Carlo modeling (Peukert et al, 2020). Furthermore, Gilles et al showed that the GNPs were highly effective in producing ROS that caused plasmid DNA damage, encouraging for mechanistically understanding radiosensitization.…”
Section: Physicochemical Mechanismsmentioning
confidence: 79%
See 1 more Smart Citation
“…This is likely due to passivation of the solid liquid interfacial catalysis of radicals, and/or absorption of secondary electrons emitted from the nanoparticle within the coating layer. The latter mechanism was supported by data showing a decrease in yield with increasing coating atoms, and has been further supported by Monte Carlo modeling (Peukert et al, 2020). Furthermore, Gilles et al showed that the GNPs were highly effective in producing ROS that caused plasmid DNA damage, encouraging for mechanistically understanding radiosensitization.…”
Section: Physicochemical Mechanismsmentioning
confidence: 79%
“…GNP coating composition and thickness has been shown to play a major role in reducing radiolysis of water surround nanoparticles due to the inability of secondary electrons generated in the GNP being able to escape through the coating, as shown theoretically (Peukert, Kempson, Douglass, & Bezak, 2020) and experimentally (Le Goas et al, 2019). In the absence of radiation, protein corona has also been shown to reduce generation of ROS from TiO 2 nanoparticles by passivating the catalytic capability at the NP‐liquid interface (Runa, Lakadamyali, Kemp, & Payne, 2017).…”
Section: Physicochemical Mechanismsmentioning
confidence: 98%
“…The nanoparticle geometry consisted of clusters of 15 nm nanoparticles constructed from in vitro measurements of GNP clustering within HeLa cells [ 16 ]. Bare 15 nm GNPs were chosen to be modelled as a previous optimisation study by the authors [ 28 ] showed that 15 nm is an optimal GNP size to maximise enhancement, providing a balance of gold mass and limited self-absorption of secondary electrons within the GNPs. The study also showed that thicker nanoparticle coatings reduced the enhancement by absorbing secondary electrons produced within the gold core preventing their contribution to the dose and reactive species yield outside of the nanoparticle.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work by the current authors, an optimisation study of GNP characteristics was performed to maximise the radiolysis yield enhancement [ 28 ]. This study was the first application of the simulation framework developed by the authors using the Geant4 Monte Carlo toolkit [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation